MODEL KEPEMIMPINAN KEPALA SEKOLAH DALAM INTERNALISASI KEBIJAKAN PENDIDIKAN DI SD NEGERI DAN SD SWASTA - Siti Khotimah (STKIP Subang, 2026)
This study aims to analyze the characteristics of principals' leadership mindset, the strategies for internalizing educational policies, the factors influencing the internalization process, and the effectiveness of educational policy implementation at SD Negeri Kalirejo Bangil and SD Islam KHA. Wakhid Hasyim Bangil. This research employed a qualitative approach using a multi-case study design. Data were collected through in-depth interviews, observations, and document analysis involving principals, teachers, educational staff, and other stakeholders. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data condensation, data display, conclusion drawing, as well as within-case and cross-case analyses. Data validity was ensured through source and technique triangulation. The findings reveal that the principals of both schools demonstrate a leadership mindset oriented toward change, educational quality improvement, and the development of a positive school culture, although these orientations are implemented differently according to the characteristics of each institution. The internalization strategies include intensive communication, exemplary leadership, teacher development, academic supervision, strengthening school culture, and involving all school members in implementing educational programs. Supporting factors include teachers' commitment, a conducive school culture, stakeholder support, and participative leadership, while inhibiting factors consist of differences in understanding, time constraints, administrative workload, and resistance to change. Although the implementation of educational policies in both schools has been effective, different approaches are evident. SD Negeri Kalirejo Bangil emphasizes bureaucratic, coordinative, and administrative aspects, whereas SD Islam KHA. Wakhid Hasyim Bangil prioritizes cultural, religious, and family-oriented approaches in the policy internalization process. This study concludes that the successful internalization of educational policies is determined by the principal's ability to build collective awareness, foster a positive organizational culture, and create synergy between educational policies and the characteristics of the school environment.